PCSK9 inhibitors and dyslipidemia: The clinical evidence - Norata, Giuseppe (2014)
Elevated plasma LDL cholesterol (LDL-C) levels are associated with cardiovascular diseases and statin therapy was proven to decrease LDL-C and reduce cardiovascular death. However, in patients at high cardiovascular risk, achievement of optimal LDL-C levels is challenging, and therefore additional strategies for further lowering LDL-C levels are under development. Recently, silencing of apolipoprotein B gene and MTP inhibition have been approved for the treatment of patients with familial hypercholesterolemia, and there is great interest in the inhibition of proprotein convertase subtilisin/kexin 9 (PCSK9). PCSK9 promotes the degradation of the LDL receptor. The inhibition of PCSK9 favors LDL catabolism and reduces plasma LDL-C levels. Monoclonal antibodies against PCSK9 represent so far the most advanced approach in clinical development, with alirocumab, evolocumab and bococizumab under advanced clinical development. Recent data from the first phase III studies show LDL-C reduction in monotherapy and on top of statins. Long-term studies on cardiovascular endpoints are ongoing and the results will be crucial to translate the benefit of this promising approach into clinical practice. © 2014 Il Pensiero Scientifico Editore.